2018
DOI: 10.1038/s41586-018-0603-3
|View full text |Cite
|
Sign up to set email alerts
|

A slow-cycling LGR5 tumour population mediates basal cell carcinoma relapse after therapy

Abstract: Basal cell carcinoma (BCC) is the most frequent cancer in humans and results from constitutive activation of the Hedgehog pathway 1 . Several Smoothened inhibitors (Smoi) are used to treat Hedgehog-mediated malignancies, including BCC and medulloblastoma 2 . Vismodegib, a Smoi, leads to BCC shrinkage in the majority of the BCC patients 3 , but the mechanism by which it mediates BCC regression is currently unknown. Here, we used two different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
121
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 120 publications
(124 citation statements)
references
References 34 publications
3
121
0
Order By: Relevance
“…Importantly, re-administration of vismodegib to mice with relapsing BCCs led again to tumour regression. 3 These findings in mice correlate well with the clinical observation; in a patient with locally advanced BCC, we report complete response upon vismodegib treatment and BCC relapse after discontinuation. Upon a second cycle of vismodegib rechallenge, complete clinical response was obtained again, suggesting a sequence of reversible and re-inducible events and proposing that the readministration of the same Hedgehog inhibitor may be efficacious for BCC recurrence in a previously responding patient.…”
supporting
confidence: 88%
See 3 more Smart Citations
“…Importantly, re-administration of vismodegib to mice with relapsing BCCs led again to tumour regression. 3 These findings in mice correlate well with the clinical observation; in a patient with locally advanced BCC, we report complete response upon vismodegib treatment and BCC relapse after discontinuation. Upon a second cycle of vismodegib rechallenge, complete clinical response was obtained again, suggesting a sequence of reversible and re-inducible events and proposing that the readministration of the same Hedgehog inhibitor may be efficacious for BCC recurrence in a previously responding patient.…”
supporting
confidence: 88%
“…The drug-tolerant persisting lesions induced by vismodegib (preneoplastic lesions of hyperplasia and dysplasia) were not mediated by Smo mutations, neither with loss of primary cilia. 3 Two independent publications showed that HPI agent vismodegib mediated tumour cell persistence, via a shift in tumour cell identity (transcriptional program resembling that of stem cells of the interfollicular epidermis and isthmus, instead of the hair follicle bulge) and activation of the Wnt pathway, revealing the key role of this pathway in BCC persistence, 3 in addition to its complex crosstalk with the Hedgehog signalling pathway during hair follicle morphogenesis and normal hair cycling. 4 Tumour cell persistence induced with vismodegib was fully reversible upon vismodegib withdrawal in mouse models, and there was tumour regrowth.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…These tumor cells reactivated the Hh pathway and resumed growth upon vismodegib discontinuation . Moreover, readministration of vismodegib in mice with relapsing BCCs led again to tumor regression . These findings in mice correlate well with the clinical observation in a patient with locally advanced BCC that discontinued vismodegib after complete response because of alopecia (Fig.…”
Section: Evaluations For Tumor Response: Clinical Follow‐up and Imagingsupporting
confidence: 75%